The Effect of the Perceived Information Richness Features of Portal on its Usage Rate and loyalty with the Mediating Role of Satisfaction - Reza Farhadpoor, Mohammad; Saatsaz, Sara (Bibliotecas. Anales de investigación, 2021)
Objectives: This study aimed to investigate the effect of perceived information richness of the National Iranian South Oil Company portal on its users’ usage rate and loyalty with the mediating role of satisfaction. Design/Methodology/Approach: Applied research was conducted using a causal-correlation survey approach. As a research sample 378 people was selected from 25000 users of by simple random sampling and complete the researcher-made questionnaire with face-validity and reliability (α = 0.83). Results/Discussion: The results showed that satisfaction (mean=3.179), loyalty (mean = 3.467), and different information richness features such as transparency (mean = 3.769), timeliness (mean = 3.78), interactivity (mean = 3.234), quick feedback (mean = 3.231), quality (mean = 3.936) and accessibility (3.662) are above average and relatively favorable. Conclusions: The results showed that among the features of the portal’s richness of information, the quality, interactivity, accessibility, and timeliness affect the usage rate of the portal and their loyalty mediated by satisfaction Originality/Value: Users’ loyalty and use of web portals is one of the factors affecting their viability. Therefore, it is necessary to consider the factors affecting them. In this study, information richness features are considered as effective factors.